TINJAUAN HUKUM HUMANITER MENGENAI PERLINDUNGAN HAK ASASI MANUSIA BAGI PERSONIL MILITER YANG MENJADI TAWANAN PERANG - Girsang, Ivan Donald; Pasek Diantha, I Made; Budi Arsika, I Made (Kertha Negara : Journal Ilmu Hukum, 2013)
Military personnel are someone who is armed and prepared to do battle or war-fighting within the framework of the defense and security of the State. In times of war or the armed conflict International has a status of military personnel, among others, as a prisoner of war when the military personnel had arrested by an enemy state. During the military personnel became prisoners of war there is protection afforded by Own Country, State retaining / enemies, Protecting Power, the UN and the ICRC.
Keywords: Military Personel, Prison of War, Protection Prison of War